REZIM INTERNASIONAL LINGKUNGAN HIDUP DAN EPISTEMIC COMMUNITY DALAM PROGRAM REDUCING EMISSION FROM DEFORESTATION AND FOREST DEGRADATION+ DI JAMBI - ., Haryadi (Jurusan Ilmu Sosial dan Ilmu Politik Fakultas Hukum Universitas Jambi, 2017)
Climate change is considered a global threat by the international community. Scientists represent by UN IPCC agree that climate change very significant cause is from the high rate of deforestation and forest degradation that occurs in forested countries. The notion of avoiding deforestation as a climate change mitigation strategy. causing REDD Programme emerged as a new mechanism for carbon sequestration and avoided emissions of developing countries. REDD + is based on the idea that countries in the developing countries would be paid to increase carbon stocks by way of new measures on forest governance according to some references in the level of international policy. As one of the potential forest owners and also has ratified the Kyoto protocol before, Indonesia once again participate in this program, one of the provinces that serve as a pilot project is Jambi. Jambi province is considered to have the potential for enormous opportunities for reducing emissions that can contribute to the success rate of carbon emission reduction nationwide. The involvement of multiple agencies or epistemic community experts in support of this program so that the program applied, showed recognition of the strategic position of this province as a forest owner who could contribute to the achievement of national emissions reduction figures also globally. This study used a qualitative method with case studies, and collecting data from informants selected purposively. The concepts used in this study is the International Regime and epistemic communities. The findings of this study was showed the influence of the International Regime environment with its epistemic community provides a very important role for the implementation and sustainability of REDD + Program in the province.